La cohésion dans les textes narratifs : analyse d’un corpus d’apprenants - Dekhissi, Laurie; Valetopoulos, Freiderikos (Studia Romanica Posnaniensia, 2019)
In this paper, we propose the study of the cohesion in the narrative texts written by B2 and C1 level learners of French as a FL. We will focus on the sentence connectors. We will analyse different parameters such as the frequency and variety of connectors used. We will then focus on some unexpected uses found in the learner corpus Corpus-CFLE. Our aim is to study the students’ narrative productions and their knowledge in the use of specific connector according to the type of the text produced.